2014
DOI: 10.1103/physreve.90.063308
|View full text |Cite
|
Sign up to set email alerts
|

Rényi information flow in the Ising model with single-spin dynamics

Abstract: The n-index Rényi mutual information and transfer entropies for the two-dimensional kinetic Ising model with arbitrary single-spin dynamics in the thermodynamic limit are derived as functions of ensemble averages of observables and spin-flip probabilities. Cluster Monte Carlo algorithms with different dynamics from the single-spin dynamics are thus applicable to estimate the transfer entropies. By means of Monte Carlo simulations with the Wolff algorithm, we calculate the information flows in the Ising model w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The information theoretical quantities such as the Shannon entropy, the mutual information, the cross entropy and the transfer information are widely used in several fields such as the financial markets [18,19], the human collective decision-making [20], the detection of the phase transition [13,21] and so on. There is another interesting information theoretical approach is the persistent homology analysis [22][23][24] which has been applied to the effective Polyakov-line model [17] which has close relation with the Potts model and also QCD; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The information theoretical quantities such as the Shannon entropy, the mutual information, the cross entropy and the transfer information are widely used in several fields such as the financial markets [18,19], the human collective decision-making [20], the detection of the phase transition [13,21] and so on. There is another interesting information theoretical approach is the persistent homology analysis [22][23][24] which has been applied to the effective Polyakov-line model [17] which has close relation with the Potts model and also QCD; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Xue's group reported that a monolayer FeSe lm grown on the SrTiO 3 (001) substrate (1 uc-FeSe/STO) shows a superconducting gap as large as 20 meV [7], suggesting that the T C of the 1 uc-FeSe/STO could be signi cantly enhanced from the T C ∼8 K of the bulk FeSe [9], possibly reaching 77 K, the boiling temperature of liquid nitrogen. Following the work, several angle-resolved photoemission spectroscopy (ARPES) studies [10][11][12][13] and transport measurements have reached the consensus that the T C of 1 uc-FeSe/STO can be as high as 65 K [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The specifics of Rényi transfer entropy is given by the fact, that it is possible to focus on information transfer of certain parts of probability distributions. Since that, Rényi transfer entropy has found several applications, e.g., in signal processing [36] or single-spin dynamics [37]. The topic of information transfer remains still a hot topic of ongoing research [38][39][40].…”
Section: Introductionmentioning
confidence: 99%